Paris, Real Estate, and Histories of Capitalism - FITZ-GIBBON, DESMOND (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
Selling Paris offers a superb inquiry into the particular institutions and agencies of late nineteenth-century French commercial real estate. This review assesses the contribution of the book in light of recent debates on the “history of capitalism” and argues that it addresses three important questions about the process of market formation, the qualities that make real estate so revealing of tensions within capitalist development, and the chronology of real estate markets and French urban development.